Variations in conformational stability and thermodynamics of the 28-kDa and a pseudo-26-kDa glutathione transferases from Schistosoma haematobium - Seeletse, Malefo Tshepiso (My University, 2024)
Schistosomiasis is a neglected tropical disease caused by blood flukes of the genus Schistosoma, affecting over 240 million individuals worldwide. The key detoxification enzymes of the parasite, glutathione-S-transferases (GSTs), play a crucial role in its survival by helping it evade the host immune system. Two isozymes, the Schistosoma haematobium 28- kDa glutathione transferase and the Schistosoma bovis/haematobium 26-kDa glutathione transferase are expressed during the parasite's life cycle, and the reason for encoding two similar enzymes within the genome is not fully understood. This study aims to comprehensively investigate and reveal the conformational stability and thermodynamics variations of the 28-kDa and a pseudo-26-kDa glutathione transferases from Schistosoma haematobium. Recombinant Sh28GST and Sbh26GST were overexpressed in Escherichia coli T7 cells and purified using immobilised metal affinity chromatography. The specific activity of the enzymes was determined using glutathione-1-chloro-2.4-dinitrobenzene (GSH-CDNB) assay, which was subsequently employed for Michaelis Menten kinetics of the two GSTs. The secondary structure of each enzyme was evaluated using far-ultraviolet (UV) Circular Dichroism (CD) and the tertiary structure using intrinsic tryptophan and extrinsic ANS fluorescence, in the presence and absence of urea. The conformational stability of the two GSTs was assessed under two different denaturing conditions: chemically induced denaturation using urea and far-UV CD, as well as heat-denaturing studies using Differential Scanning Calorimetry. Both proteins were successfully overexpressed, and high yields of purity were achieved. The secondary structural content of both proteins was predominantly alpha-helical. The tertiary structure showed that both proteins had most of their tryptophan residues exposed to the polar environment, and fluorescence spectra resulted in minor intensity changes from native to denatured protein. The specific activity of each enzyme was determined to be 40 μmol/min/mg for Sbh26GST and 67 μmol/min/mg for Sh28GST, indicating that Sh28GST had the higher specific activity among the two enzymes. Furthermore, when comparing their overall catalytic efficiency, Sbh26GST exhibited a higher value of 200 mM-1min-1 , whereas Sh28GST showed a lower catalytic efficiency of mM-1min-1 . Conformational stability and thermodynamics studies revealed interesting findings: Sbh26GST was more stable in the presence of urea, while Sh28GST was more stable in the presence of heat. Our collective findings led us to conclude that greater chemical denaturant stability observed in a protein does not always correlate with its stability in the presence of heat. These findings were attributed to the number and location of tryptophan residues found in each GST
A research report submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2023
Keywords: Schistosomiasis; Blood flukes; Glutathione-S-transferases (GSTs)